(untitled) (San Diego, CA, 1998)
Fish Respiration synthesizes classical literature and highlights recent developments pertaining to the respiratory physiology of fishes. Compiled by a team of international researchers, this comprehensive and authoritative review of the respiratory physiology of fishes will appeal to any comparative physiologist interested in this subject.
Sinh lý động vật thủy sản
Keywords: Fish respiration,Sự hô hấp ở cá